2020
DOI: 10.3238/arztebl.2020.0583
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability of Task-Shifting from Doctors to Allied Health Professionals

Abstract: ask-shifting from doctors to members of various non-medical specialized professions is routine practice in the Anglo-Saxon countries and Scandinavia (1, 2). In Germany only narrowly defined medical tasks (MT) are delegated, mostly to Qualified Medical Practice Assistants (MPA) (eBox) (3,4). Although the concept of redistributing certain medical activities has existed since 1975 (5), the requirements, as well as the services eligible for delegation, were first defined in 2013 (6). The prerequisite of delegating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…Furthermore, the data were collected by telephone, and only people with a landline were contacted [ 7 , 23 ]. This might have resulted in a higher proportion of older persons being reached [ 46 ]. Older people refused to answer the question about the most important tasks of PNs more often than younger people (in both groups) and lower educated people more often than higher educated people (in the inexperienced group).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the data were collected by telephone, and only people with a landline were contacted [ 7 , 23 ]. This might have resulted in a higher proportion of older persons being reached [ 46 ]. Older people refused to answer the question about the most important tasks of PNs more often than younger people (in both groups) and lower educated people more often than higher educated people (in the inexperienced group).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our confidence in the finding that older people accept delegation is low and other research on this matter is also ambivalent. A recent representative survey in Germany showed that the majority of adults accept the shifting of medical tasks to medical practice assistants, but the acceptance varied depending on the specific task (in favor of minor illnesses), and adults aged 65 and over tended to be more unwilling [ 56 ]. There are also indications that further variables need to be explored to understand older people’s preferences.…”
Section: Discussionmentioning
confidence: 99%
“…In Deutschland hingegen ist die Primärversorgung stark ärztlich geprägt. Die Bereitschaft zur Anwendung von Delegationsmodellen hat in den letzten Jahren zugenommen 14 , hängt jedoch auch von den gesetzlichen Bestimmungen ab 15 . Konkrete Ansätze für die Umsetzung von Delegationsmodellen stellen Qualifizierungsmaßnahmen für Medizinische Fachangestellte (MFA) dar 16 .…”
Section: Hintergrundunclassified